El marketing mix y su relación en la satisfacción del cliente en el Hotel Época Boutique – Iquitos 2023 - Campos Ramirez, Joham Eduardo (2024)
The objective was to determine the relationship between the marketing mix and customer satisfaction at the Época Boutique Hotel - Iquitos 2023. The methodology used in this research was a correlational, descriptive, non experimental design. The sample consisted of 117 customers of the Época Boutique Hotel. The results obtained were: The multivariate analysis of the dimensions determined that the marketing mix is related to the dimensions of customer satisfaction, with Spearman's Rho test it was determined that the product is related to the level of satisfaction and expectation (with p=0.040, p=0.016) respectively. Price is related to functional performance, with satisfaction and expectation levels with (p= 0.044, p= 0.000 and p=0.003) respectively. The Plaza dimension is related to functional performance and expectation with (p=0.016 and p= 0.046) respectively, and Promotion is related to satisfaction level and expectation with (p= 0.020 and p=0.006) respectively.